The Role of AI in the Digital Skill Development of Employees in SMEs - D'Costa, Catherine Sonali (My University, 2025)
This thesis explores the transformative role of Artificial Intelligence (AI) in the digital skill development of employees within Small and Medium-sized Enterprises (SMEs), a sector that often faces unique constraints and opportunities in adopting emerging technologies. In the context of ongoing digital transformation, SMEs are increasingly pressured to equip their workforce with relevant digital competencies. AI, widely recognized for its potential to transform work processes, is also emerging as a tool for informal learning and skill enhancement. This study investigates how AI contributes to the digital skill development of employees and assists them in adapting to the ongoing digital transformation. A qualitative research approach has been adopted, with data collected through semi-structured interviews conducted with employees, managers, and executives from five SMEs in Finland. These case firms span industries such as software development, consulting, and manufacturing. The study draws from thematic analysis to identify key patterns and interpret the human-centered dynamics of AI integration in workplace learning. The research is grounded in a theoretical framework that links employee skills development to technological advancement, emphasizing digital literacy, organizational readiness, and ethical AI governance. The study reveals that AI functions primarily as an informal, supportive learning tool rather than a formal training system. Employees use AI applications such as generative models, chatbots, and code assistants to enhance productivity, access just-in-time learning, and foster self-directed development. This has reduced reliance on traditional mentorship models and encouraged independent problem-solving. However, effective integration is closely linked to foundational digital literacy and a willingness to engage in continuous learning. Furthermore, concerns regarding data privacy, algorithmic bias, and ethical usage highlight the importance of governance frameworks in supporting responsible AI adoption. The study contributes to the literature by extending theoretical discussions on workforce upskilling in the AI era and emphasizing the need for inclusive, adaptive learning environments. The research highlights the importance of top management support, investment in digital literacy, and the implementation of ethical AI practices. The findings underscore the need for future studies to explore the long-term impacts of AI-facilitated skill development. Ultimately, the study concludes that while AI is a powerful enabler of digital skills, its success hinges on strategic alignment with technological advancement and a human-centered approach to workforce development.
Keywords: employees; digitalisation; small and medium-sized enterprises; artificial intelligence; digital competence; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development